Clinical results of using a silver-containing preparation as part of an antimicrobial spacer in the treatment of periprosthetic hip joint infection - Svetlana A. Bozhkova; Magomed Sh. Gadzhimagomedov; Rashid M. Tikhilov; Vasily A. Artyukh; Alexander P. Antipov; Alexander V. Afanasyev; Sergey S. Toropov; Yulia V. Muravyeva (Гений oртопедии)
Introduction Periprosthetic infection (PPI) is one of the most serious complications of primary arthroplasty. Its rates range between 1.1 and 2 %. This study presents a comparative analysis of the results of the sanitizing stage of two-stage treatment of patients with chronic PPI of the hip joint (HJ) using an antimicrobial spacer impregnated with highly dispersed silver and without its impregnation. Purpose To conduct a comparative analysis of the clinical efficacy of using HD-Ag for impregnation of an antimicrobial spacer in patients with chronic PPI HJ during the sanitizing stage. Materials and methods A retrospective study is based on the analysis of the treatment outcomes of 223 patients with PPI HJ with antimicrobial spacers implanted during the sanitizing stage. Two groups of patients were formed based on the impregnation of bone cement with only an antibiotic or its combination with HD-Ag, group 1 (n = 112) and group 2 (n = 111), respectively. The evaluation of the treatment outcomes at a follow-up period of at least 2 years was carried out in accordance with the modified Delphi criteria. The reliability of differences in quantitative parameters between the groups was analyzed using nonparametric Mann – Whitney test, whereas Fisher test was used to analyze relative indicators. The differences were considered significant at p < 0.05. Results The spectrum of pathogens was comparable in both groups. The recurrence rate in groups 1 and 2 was 23.2 % and 17.1 %, respectively (p > 0.05), while for monobacterial infection caused by gram-positive bacteria it was significantly lower in group 2 (p = 0.012). Discussion As reported, the recurrence rate of periprosthetic infection varies from 8 to 40 %, depending on the nature of the infectious process and the type of pathogen. In the group with the use of HD-Ag as part of an antimicrobial spacer, the effectiveness of the sanitizing stage was 82.9 % and in the comparison group it was 76.8 %. However, a subanalysis of the effect of the etiology of PPIs on treatment results showed that the use of AM-spacer with a combination of silver and vancomycin led to a statistically significant reduction in the risk of recurrence in patients with monobacterial infection caused by gram-positive pathogens and provided arrest of infection in 89.7 % of cases. Conclusion In the sanitizing stage of two-stage treatment of chronic peri-implant hip infection caused by gram-positive bacteria, the antimicrobial cement spacer impregnated with highly dispersed silver showed high efficiency. However, further development of new combinations for bone cement impregnation is required to expand the spectrum of antimicrobial activity of the spacers.